1960
DOI: 10.1128/jb.80.5.639-647.1960
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Cell Walls of the Agent of Meningopneumonitis

Abstract: It is recognized that microorganisms of the psittacosis group are contained within a rigid envelope (Hamre, Rake, and Rake, 1947) which is highly resistant to enzymes (Brown, Itatani, and Moulder, 1952) and mechanical disintegration (Ross and Gogolak, 1957). With the demonstration that penicillin inhibits the growth of bacteria by interfering with cell wall synthesis (Park and Strominger, 1957; Hahn and Ciak, 1957; Lederberg, 1957), the susceptibility of members of the psittacosis group to penicillin (Hurst, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…The existence of cell walls similar in many respects to those of bacteria was suggested by the inhibition of Chiamydia by penicillin (5, 12,15) and was demonstrated directly by the isolation and partial chemical analysis of the envelopes of these organisms (2,4,8). This similarity to bacteria suggested that the envelope should consist of a cell wall and cytoplasmic membrane, but such structures have not been previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of cell walls similar in many respects to those of bacteria was suggested by the inhibition of Chiamydia by penicillin (5, 12,15) and was demonstrated directly by the isolation and partial chemical analysis of the envelopes of these organisms (2,4,8). This similarity to bacteria suggested that the envelope should consist of a cell wall and cytoplasmic membrane, but such structures have not been previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…1 (lanes a and b) that there is little difference between crude and purified elementary bodies of C. psittaci, and, even in these whole cell preparations, the most prominent feature is a protein band with a molecular weight of approximately 43,000, hereafter referred to as the major protein. This major protein remained the dominant feature of cell envelopes of C. psittaci elementary bodies prepared by the alkali-EDTA method of Narita and (10). from each lane in Fig.…”
mentioning
confidence: 88%
“…Metabolism and lipid analysis of a number of chlamydia agents cultivated in chicken embryos and cell culture has been previously reported by several investigators (11,13,17,20). Jenkin (1) reported that the purified Chlamydia psittaci strain meningopneumonitis (MN) contained a large amount of lipid (about 40% by dry weight).…”
mentioning
confidence: 93%